EVALUATION OF IN VITRO CONDITIONS INFLUENCING PHOSPHATIDYLINOSITOL-SPECIFIC PHOSPHOLIPASE C PRODUCTION BY STAPHYLOCOCCUS AUREUS ATCC 9144 - DEEPALI K. KOTHEKAR; DEBJANI DASGUPTA (International Journal of Pharma and Bio Sciences, 2013)
The aim of this study was to evaluate the growth conditions affecting production of hosphatidylinositol-specific phospholipase-C (PIPLC) by Staphylococcus aureus ATCC 9144. A simple colorimetric method for direct estimation of phospholipids was adapted for rapid assaying of PIPLC. First phase of the study involved preliminary screening of nutritional and physical parameters. In the second phase, Plackett-Burman statistical design was employed to identify the most critical factors. Of the eleven variables studied, peptone, sodium carbonate (buffer), and rotational speed exhibited significant positive influence while glucose showed a negative influence on PIPLC activity. Thus, low C/N ratio, aeration, and buffering agent were identified as important factors controlling production of PIPLC. These results contribute to the existing knowledge on PIPLC regulation in Staph. aureus and would help optimize production of this enzyme for its successful application in biochemical research and industry.